Brain magnetic resonance imaging findings of pediatric hemophagocytic lymphohistiocytosis could be diagnostic and life-saving - Aydın, Kürşad; Kılıç, Betül; Topçu, Yasemin; Telhan, Leyla; Dolu, Merve Hilal; Kartal, Ayşe (Elsevier Inc., 2022)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rare and fatal disease and may also present with central nervous system findings at the beginning without specific diagnostic criteria. Brain magnetic resonance imaging (MRI) findings are diverse and can also be diagnostic. We aimed to emphasize the importance of brain MRI findings in the early diagnosis of this fatal disease. Methods: MRI findings, clinical presentations, treatment response, and prognosis of seven patients with HLH were described. Results: There were seven pediatric patients who were initially diagnosed with HLH with neurological findings without systemic signs of HLH: four as primary, two as secondary, and one as possible primary HLH. All patients had contrast-enhancing diffuse cerebellar and brainstem lesions; patchy periventricular and callosal cerebral lesions were observed. Thalamus involvement was found in three (42.8%), corpus callosum involvement in six (85.7%), and cervical spinal involvement in one (14.2%). Patients were followed up with these MRI findings, with prediagnoses of toxic, metabolic, infectious, vascular, and demyelinating diseases. Not all patients met the HLH diagnostic criteria due to incomplete systemic/laboratory findings; therefore, only two were immediately directed for hematopoietic stem cell therapy. Four died shortly after admission, one patient could not be followed up after HLH treatment, and two patients who fulfilled the HLH diagnostic criteria underwent hematopoietic stem cell transplantation and survived. Conclusions: Brain MRI findings, especially in the presence of neurological findings, allow for early diagnosis, which can be life-saving. These common features in brain MRI findings should be evaluated with this suspicion and included in HLH diagnostic criteria.
Keywords: Brain MRI Findings; Central Nervous System; Diagnosis; Hemophagocytic Lymphohistiocytosis